Unifying Tables, Objects and Documents - Schulte, Wolfram (Proceedings of Declarative Programming in the Context of OO Languages (DP-COOL 2003), 2003)
This paper proposes a number of type-system and language extensions to natively support relational and hierarchical data within a statically typed object-oriented setting. In our approach SQL tables and XML documents become first class citizens that benefit from the full range of features available in a modern programming language like C] or Java. This allows objects, tables and documents to be constructed, loaded, passed, transformed, updated, and queried in a unified and typesafe manner.
Appeared